Perbandingan Tingkat Stres pada Mahasiswa Tingkat I, II dan III Fakultas Kedokteran Universitas Lampung - Nabila Casogi Adryana; Oktafany; Ety Apriliana; Dwita Oktaria (Majority, 2020)
Stress is a condition of physical, emotional, mental and spiritual disability in response to a threat causing physical health problems. College students are the individuals who are prepared to be globally competitive as human resources. The aim of the study is to determine the comparison of stress level in the first, second, and third year students of Medical Faculty of University of Lampung.This study was a analytical descriptive study using cross sectional design and proportionate stratified random sampling as sampling method. Questionnaires was used as measuring instrument. The data was analyzed using one-way ANOVA.The data were assessed in total 312 subjects as respondent, and accounted of 102 in the first, 100 in the second, and 98 in the third year. A percentage of 76.5% of moderate stress and 23.5% of severe stress were obtained from the first year ofstudents. The subjects of the second year were 82% of moderate stress and 18% of severe stress.The subjects of 98 of the third year own 65.3% of moderate stress and 34.7% of severe stress. One-way ANNOVA test results showed p value of 0,001. There was a comparison of stress levelin the first, second, and third yearstudents of Medical Faculty of University of Lampung. This study showed a comparison of stress level in the first, second, and third year students of Medical Faculty of University of Lampung.